The Effect of Revenue Effectiveness and Efficiency of Regional Expenditure on SiLPA in Indonesia - Sitompul, Gabriel Amadeus; Lubis, Irsad (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The performance-based APBD structure allows for the existence of Budget Calculation Surplus (SiLPA) at the end of the fiscal year which is the remaining budget funds that can be used by local governments as a source of revenue financing for the next fiscal year. In this study, there is a goal to determine how the effectiveness of regional revenue and the efficiency of regional spending on the remaining excess budget calculations in 34 provinces in Indonesia in 2017 - 2020. This study uses descriptive quantitative research with the data used is secondary data. And using the panel data regression analysis method which is processed with the eviews version 12 data processing application. The results showed that the variables of regional revenue effectiveness and regional expenditure efficiency had a significant positive effect on SiLPA in Indonesia in 34 provinces in 2017-2020.